Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae) - Poupin, Joseph; Crestey, Nicole; Guelte, Jean-Paul Le (Zootaxa, 2018)
Sesarmid crabs of the genus Karstarma Davie & Ng, 2007 are reported for the first time in the Western Indian Ocean: they were discovered in the lava tubes of the volcano ‘Piton de la Fournaise’, Réunion Island. A new species, morphologically similar to Karstarma jacksoni (Balss, 1934) from Christmas Island, Eastern Indian Ocean, is recognized and described. A redescription of K. jacksoni is also provided. A second species is recognized, but being represented in the collection by a single juvenile, it cannot be identified to species level until more collections are made in the lava tubes. [Zoobank: http://zoobank.org/NomenclaturalActs/C70A95B2-D667-491D-BD35-5DF32E3FFB08]